"Shith descended to the depths”: the Baraita in the Talmuds and its relation to the Tosefta - Shushtri, Rabin (Hebrew Union College annual / Jewish Institute of Religion, 2011)
This article deals with a tradition in Tosefta Sukkah and its relation to a parallel baraita in the Talmuds. The tradition, as it appears in the Tosefta, includes both halachic and aggadic content together, regarding the shith in the Temple. On the other hand, the Talmuds omit one of the halachic statements in the tradition and even separate halachic and aggadic content into two different baraitot . A detailed inspection of the Talmuds reveals that the tradition, as it appears in the Tosefta, was known to the Talmuds, but was edited and altered within them. A study of the various Babylonian traditions of the sugya shows that the reason for this editing was the testimony of R. Eleazar bar Zadok, which prevailed to the extent that legal statements that conflicted with it were not cited. At the same time, it seems that the talmudic editors perceived the legend concerning the shith as figurative and unrealistic, so that it was not deemed to be problematic when juxtaposed with the statement of R. Eleazar. At a later stage in the development of the sugya , the legend came to be viewed as realistically plausible, and it was compared with a mishnaic tradition in Me'ilah . The editing of this baraita did not stop at that point, but was continued in the Babylonian Talmud.